Effect of traditional Chinese exercise combined with massage on pain and disability in patients with lumbar disc herniation: A multi-center, randomized, controlled, assessor-blinded clinical trial - Zhou, Xin; Kong, Lingjun; Ren, Jun; Song, Pengfei; Wu, Zhiwei; He, Tianxiang; Lv, Zhizhen; Zhang, Shuaipan; Sun, Wuquan; Zhang, Jiafu; Cai, Junhao; Zhu, Qingguang; et al. (Frontiers in Neurology, 2022)
Background: Herniation of the nucleus pulposus caused by disc degeneration and other reasons can cause low back pain and disability. In China, traditional Chinese exercises (TCEs) and traditional Chinese massage (TCM) are widely used to improve symptoms of pain and disability in patients with lumbar disc herniation (LDH). The safety and efficacy of combination therapy have not been studied. Objectives: To assess the effect of traditional Chinese exercise combined with massage vs traditional Chinese massage alone on pain, disability, lumbar mobility, and gait performance in patients with LDH. Objectives: To assess the effect of traditional Chinese exercise combined with massage vs traditional Chinese massage alone on pain, disability, lumbar mobility, and gait performance in patients with LDH. Methods: Multi-center, randomized clinical trial conducted at 4 hospitals in China and enrolled 272 patients with LDH. Participants were randomly assigned to TCEs plus TCM group or TCM alone group. The combined therapy group received 18 Tai Chi training sessions (30-minute sessions 3 times a week) and regular TCM treatments over 6 weeks. The control group received TCM therapy alone and was instructed to maintain their usual daily physical activity. Outcome variables measured included Visual Analog Scale (VAS), Short Form of McGill Pain Questionnaire (SF-MPQ), Oswestry Disability Index (ODI), lumbar spine range of motion (ROM), and gait performance. Results: Among the 272 randomized participants, 259 completed the study. The reduction in the VAS score at week 6 was greater in the TC group than in the TCM group with a mean difference of 4.05 (95% CI, 2.15-5.95; P < 0.001), and the ODI score with between-group differences of 3.57 points (95% CI, 2.84-4.30 points; P < 0.001). Similar significantly different results were observed in SF-MPQ, walking speed, cadence, and lumbar ROM. No adverse events were reported throughout the study period. Conclusion: Compared with TCM alone, TCEs combined with TCM treatment performed better in reducing pain and improving disability. The combination therapy could be considered a valuable treatment option for LDH patients, with potential therapeutic utility for middle-aged and elderly patients with LDH.